Expanding Research on Decentering as Measured by the Portuguese Version of the Experiences Questionnaire - Gregório, Sónia (2015)
For long decentering has been regarded as a crucial process for well-being and health. Thus, reliable measures are needed to assess decentering. This study aimed at examining the psychometric characteristics of the Portuguese version of the Experiences Questionnaire (EQ), and to contribute to gather new evidence on the role of this particular measure of decentering on the well-known relationship between rumination and depressive symptoms. The EQ factorial structure was assessed through a Confirmatory Factor Analysis (CFA) conducted in 709 participants (66% women; 34% men). CFA' results supported a 10-item solution (χ2/df = 2.62; CFI = .96; TLI = .95; RMSEA = .05, CI = .04 to .06) with high internal consistency (α = .81), test-retest reliability (r = .86; p < .010) and construct validity. Two path analyses were further conducted in a subsample exploring the indirect effect of rumination on depression through the mechanism of decentering as assessed by the specific measure of EQ, and by the non-specific measure of decentering TMS. Decentering, only when measured by EQ, significantly emerged as a mechanism through which the relationship between rumination and depressive symptoms also operates (R 2 = .22). Findings highlight the importance of using EQ as a specific measure of this transdiagnostic process in research and clinical settings.